The Influence of Leadership on Work Motivation of PT Ground Handling Employees. Angkasa Gapura Juanda International Airport, Surabaya - Aprilia, Dhira Dwi; Laksana, Andityo Pujo (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Leadership in a company must have a creative and innovative attitude and be able to influence their subordinates, and must also be able to motivate their subordinates. Work motivation is a force within a person that influences the direction, intensity and persistence of a person's voluntary behavior to do work. One of the companies that is active in improving the leadership and work motivation of ground handling employees is PT. Gapura Angkasa Juanda International Airport Surabaya. Therefore, leadership style is very important in order to create creative, intelligent and superior human resources. This research is useful for knowing the influence of leadership on the work motivation of ground handling employees at PT. Angkasa Gapura Juanda International Airport, Surabaya. This research uses quantitative methods. The population of this research is ground handling employees of PT. Gapura Angkasa Juanda International Airport, Surabaya, totaling 439 people, while a sample of 85 respondents was taken using the Slovin formula. Data were analyzed using SPSS 23 software with simple linear regression analysis, T test, and coefficient of determination test. The results of the data analysis test showed that the significance value of variable X on Y was 0.000 0.05, which means that there is a significant and positive influence. If we look at the simultaneous R square (R^2) between variables X and Y, it can be interpreted that the influence of leadership on the work motivation of ground handling employees at PT. Gapura Angkasa Juanda International Airport Surabaya is 17.2%.